Dampak status sosial ekonomi dan kebugaran jasmani terhadap prestasi belajar siswa di Maluku Utara - Djen Djalal; Juhanis Juhanis (Seminar Nasional LP2M UNM, 2019)
This research is a type of quantitative research through an experimental approach that aims to find out; the impact of socio-economic status and physical fitness on learning achievement in senior high school students in Ternate City, North Maluku. The population is all public high school students throughout Ternate, North Maluku. The sample used was 60 male senior high school students in Ternate City, North Maluku. The sampling technique is the Proportion Sampling technique. The data collection technique in this study used a test. The instruments used in this study were socio-economic status data using questionnaires, physical fitness data using TKJI tests aged 16-19 years, and learning achievement data through semester average scores. The data analysis technique uses product moment correlation through the SPSS 21 program at a significant level α = 0.05. The results of the study show that; (1) There is a significant effect of socio-economic status on learning achievement in high school students in the entire city of Ternate, North Maluku; (2) There is a significant effect of physical fitness on learning achievement in public high school students throughout Ternate City, North Maluku; (3) There is a significant effect of socio-economic status and physical fitness on learning achievement in public high school students throughout Ternate City, North Maluku.